2009
DOI: 10.1097/md.0b013e3181a692f0
|View full text |Cite
|
Sign up to set email alerts
|

Acute Bacterial Pneumonia is Associated With the Occurrence of Acute Coronary Syndromes

Abstract: A link between acute infections and the development of acute coronary syndromes (ACS) has been proposed. We used retrospective cohort and self-controlled case series analyses to define the closeness of the association between acute bacterial pneumonia due to Streptococcus pneumoniae or Haemophilus influenzae and ACS. For the retrospective cohort analysis we included a control group of patients with admission diagnoses other than pneumonia or ACS. For the self-controlled case series analysis, we made within-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 45 publications
2
105
0
2
Order By: Relevance
“…In 32 patients, the risk of acute coronary syndrome increased 50-fold within a 15-day period after hospitalization for pneumonia. 9 Likewise, in 42 patients the risk of AMI was 35-fold higher within 2 days after the recognition of S aureus bacteremia, 6 and in 669 patients the risk of stroke was 8-fold higher within 2 weeks after infection.12 These estimates are comparable to our 20-fold increased RR versus population controls.Few data are available on the long-term risks of AMI/ AIS following infection. A case-only study by Smeeth et al 14 found that out-of-hospital respiratory tract or urinary tract infection was associated with a 1.2-fold increased risk of AMI or stroke within 29 to 91 days after infection.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…In 32 patients, the risk of acute coronary syndrome increased 50-fold within a 15-day period after hospitalization for pneumonia. 9 Likewise, in 42 patients the risk of AMI was 35-fold higher within 2 days after the recognition of S aureus bacteremia, 6 and in 669 patients the risk of stroke was 8-fold higher within 2 weeks after infection.12 These estimates are comparable to our 20-fold increased RR versus population controls.Few data are available on the long-term risks of AMI/ AIS following infection. A case-only study by Smeeth et al 14 found that out-of-hospital respiratory tract or urinary tract infection was associated with a 1.2-fold increased risk of AMI or stroke within 29 to 91 days after infection.…”
supporting
confidence: 78%
“…13,14 Only 1 cohort study of 206 patients with pneumonia included a comparison group, 9 and we are aware of only 3 studies that included microbiological test results. 6,9,10 The lack of laboratory confirmation of infection may have falsely inflated the effect estimates if cardiovascular events were initially misdiagnosed as infections. Community-acquired bacteremia (CAB) is a well-defined clinical entity that embraces a wide range of mechanisms whereby infection may trigger cardiovascular events.…”
mentioning
confidence: 99%
“…[11][12][13][14]19 However, given the likely mechanisms at play, it is expected that their development is interrelated. Musher et al 10 were the first to document that many patients with pneumonia have Ͼ1 type of cardiac event during the course of their infection.…”
Section: Discussionmentioning
confidence: 99%
“…These factors are markers of higher baseline general risk (age and nursing home residence), increased cardiovascular risk (history of heart failure, prior cardiac arrhythmias, previously diagnosed coronary artery disease, and arterial hypertension), and more severe pneumonia at presentation (respiratory rate Ն30 breaths per minute, blood pH Ͻ7.35, blood urea nitrogen Ն30 mg/dL, sodium Ͻ130 mmol/L, hematocrit Ͻ30%, pleural effusion on chest x-ray, and need for inpatient care), which is concordant with previous reports. [12][13][14] The PSI, the most widely validated tool for disease severity assessment in CAP patients, 16,17 incorporates most of these factors (except for history of prior cardiac arrhythmias, previously diagnosed coronary artery disease, and arterial hypertension). Ramirez et al 12 showed a significant correlation between PSI score and the risk of MI in hospitalized veterans with pneumonia; our study now extends this association to other cardiac events and beyond that high-risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Acute lung injury and multi-organ dysfunction syndrome, as well as acute cardiac events mostly occurring early in the course of CAP, have been identified as being significant contributors to mortality [1][2][3][4][5][6][7]. In the case of pneumococcal CAP, an increasing body of evidence, derived from both clinical and experimental studies, has implicated the major cytolytic, cholesterolbinding, pore-forming protein toxin, pneumolysin (Ply), in the pathogenesis of associated adverse pulmonary and cardiovascular events [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%